AGR543: Quantitative Methods in Agribusiness / Faculty of Plantation and Agrotechnology - UiTM, Faculty of Plantation and Agrotechnology (Universiti Teknologi MARA (UiTM), 2018)
This course deals with mathematical principles and statistical techniques used in analysis and problems in agribusiness. Attention is given to data collection, prediction of agricultural economic variables, sound sampling methods, estimation of means, standard deviation, variance, indices, graphics, regression analysis, testing hypotheses, and the use of mathematical software to do statistical procedures. Topics studied include descriptive & inferential statistics, basic and discrete probability distributions, normal and sampling distributions, confidence interval estimation, mathematical concepts, linear regression, correlation analysis, and multiple regressions. The major emphasis of the course will be on understanding and absorbing mathematical and statistical techniques which assist agribusiness managers with decision making.